2020
DOI: 10.3390/polym12102298
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Characterization of Coatings from Polyamide Powders Functionalized with Nanosilica

Abstract: Polyamide coatings are thermoplastics with great advantages such as a good corrosion protection of the base metal and wear resistance. Their application as powder coatings is an environmentally friendly option that is currently attracting growing interest. However, during their life service, they can sometimes be exposed to conditions that they are unable to stand. In this work, a polyamide 11 (PA11) powder was reinforced with different percentages of silica nanoparticles (1–3 wt. %). Powder mixtures were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 64 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…Several studies have shown that the nanoadditions of SiO 2 allow some of the properties (such as corrosion and wear resistance) of conventional liquid epoxy coatings to be improved. An increase in the mechanical properties has sometimes been reported [22][23][24] . Other studies have focused on improvement in corrosion resistance when silica mesoporous nanoparticles have been used as nanocontainers for corrosion inhibitors 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the nanoadditions of SiO 2 allow some of the properties (such as corrosion and wear resistance) of conventional liquid epoxy coatings to be improved. An increase in the mechanical properties has sometimes been reported [22][23][24] . Other studies have focused on improvement in corrosion resistance when silica mesoporous nanoparticles have been used as nanocontainers for corrosion inhibitors 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The samples were treated with three classes of coatings. Biobased commercial Polyamide (PA11) coatings called Rilsan ® [ 16 ], produced by Arkema (Rho, Milano, Italy) was deposited as powder coating, after heating the metallic samples at 200 °C. Four samples were prepared: 2 in a transparent version and 2 in the white one.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…e.g., from castor oil, thus exploiting poor and semi-arid soils not suitable for food cultivars. It is very versatile, due to the possibilities for its functionalization with silanes [ 16 ] or for blending with poly(butadiene succinate) (PBS) to obtain a partially biodegradable matrix [ 17 ]. In addition, PA11 exhibit antibacterial properties as recently demonstrated [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is of great interest due to current restrictions limiting volatile organic compounds (VOCs) in both waterbased and solvent-based products [2]. Some other advantages of these coatings are, for instance, the possibility of recovering 99 % of the powder lost during the coating process and the superior finish that this type of coating [3,4] has. In fact, it is considered to comply with the "4E principle" (environment, efficiency, ecology and economy) in the coating industry, making its development of special interest [5].…”
Section: Introductionmentioning
confidence: 99%